Solid Sr2Ti1-xMnxO4 (x = 0; 0,01; 0,025; 0,05; 0,1) solutions with K2NiF4 structure - T.I. Chupakhina; A.M. Uporova; O.I. Gyrdashova; L.Yu. Buldakova; Y.A. Deeva; I.V. Baklanova; M.Yu. Yanchenko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
Solid of Sr2Ti1-xMnxO4 (x = 0; 0.01; 0.025; 0.05; 0.1) solutions with Raddlesden-Popper structure (An+1BnO3n+1, n = 1, structural type K2NiF4) were obtained by a precursor technology. Formate complexes of the corresponding metals synthesized by an original method were used as precursors. The products of thermolysis of the obtained complexes with an organic ligand are isostructural single-phase samples, which crystallize as agglomerates with an average size of 1 μm. Using energy dispersive X-ray analysis, we established a uniform distribution in the agglomerates of Sr2+, Ti4+ and Mn4+. According to electron spin resonance and optical spectroscopy, manganese in titanium-oxygen polyhedra of Sr2Ti1-xMnxO4 is predominantly in oxidation degree 4+. Increasing the concentration of manganese in the solid solution composition effectively narrows the forbidden band width of strontium titanate from 3.5 eV to 2.5 eV for Sr2Ti0,9Mn0,1O4. The catalytic properties Sr2Ti1-xMnxO4 were analyzed in the oxidation reaction of hydroquinone under irradiation of its aqueous solutions in the ultraviolet and visible spectral ranges. Under the described conditions, all photocatalysts showed a high rate of photooxidation. It was found that the photocatalytic activity of Sr2Ti1-xMnxO4 in 3 consecutive cycles of photooxidation under infrared stimulation exceeds the commercial catalyst Degussa P25 by 4 times.